Correlation of Dance Functional Status with Lower Limb Flexibility, Power and Dynamic Balance in Recreational Ballet Dancers – A Cross-Sectional Study (Baltic Journal of Sport and Health Sciences, 2024)
Background: Paediatric ballet dancers are particularly prone to injuries due to the demanding nature of their art form, exacerbated by intensive training during crucial growth and maturation phases. The prevalence of injuries, especially those aﬀecting lower limbs, hampers dancers’ functional capacity. Unlike their professional counterparts, recreational ballet dancers lack specialized training, heightening their vulnerability. The accumulation of repetitive injuries often hampers their ability to attain the highest levels of achievement in their careers, underscoring the necessity to identify and comprehend contributing factors. The aim is to fnd a correlation between the Dance Functional Outcome Survey (DFOS) and critical factors like lower limb ﬂexibility, power, and dynamic balance among recreational ballet dancers.Methodology: 53 recreational ballet dancers aged 10–18 years with at least one year of dance experience were included. Lower limb ﬂexibility was assessed using the sit and reach test, ankle ﬂexibility, and straddle in supine tests, while power and dynamic balance were evaluated through vertical jump tests and Y balance tests. The DFOS questionnaire measured health status.Result: Results revealed statistically significant weak positive correlations between DFOS and various factors: sit and reach test (r=0.3060), ankle ﬂexibility (r=0.3830), straddle in supine (r=0.3270), vertical jump test (r=0.3250), and Y balance composite (Right: r=0.3200; Left: r=0.3420).Conclusion: This study concludes that recreational ballet dancers with greater ﬂexibility, power, and dynamic balance in the lower limb tend to exhibit a higher dance functional status.Keywords: paediatric, ballet dancers, ﬂexibility, power, dynamic balance, Dance Functional Outcome Survey.